Strategi pengelolaan sampah rumah tangga di kecamatan Bengkalis - Aldila Hasanah; Thamrin Thamrin; Ridwan Manda Putra (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2023)
Household waste is one type of waste that exacerbates the waste problem faced by the Bengkalis Government. The greater the increase in population, the greater the waste generated. There is a need for household waste management to minimize the accumulation of waste in the community. The purpose of this study is to analyze household waste management in Bengkalis District and develop strategies for household waste management in Bengkalis District. This study uses a survey method with descriptive analysis and SWOT (Strength-Weakness-Opportunities-Threats) analysis. The results of the study indicated that the management of household waste in Bengkalis District has not been fully implemented. It is necessary to develop a strategy for managing household waste. Based on the SWOT analysis, it produces a strategy of strengths and opportunities, namely the need for evaluation of waste facilities and infrastructure, human resources, waste services, household waste retribution, information systems, community participation in household waste and optimizing continuously for the community to manage household waste. ladder.